PERANCANGAN LAMPU OTOMATIS MENGGUNAKAN SENSOR CAHAYA BERBASIS ARDUINO UNO CANGGIH DAN EFEKTIF - Muhammad Putra Alfansyah; Jimmie Alfansyah (Jurnal Komputer dan Teknologi, 2026)
Energy waste caused by manually operated lights is a common problem in daily life. This study aims to design an automatic lighting system based on Arduino Uno using a light sensor (LDR) to turn the lights on and off according to ambient light intensity. The method applied is experimental, including hardware design (Arduino Uno, LDR, resistor, relay, LED light) and software programming using Arduino IDE. The system reads sensor data, processes it, and controls the lights automatically based on a set light threshold. Testing was conducted by simulating day and night conditions. The results show that the lights turn on when ambient light is low and turn off when sufficient, operating responsively and efficiently. This system improves user convenience and reduces energy consumption. The implementation of Arduino-based automatic lighting provides a practical and energy-saving solution for adaptive illumination.